Case Report: Termination of unplanned pregnancy led to rapid deterioration of non-small-cell lung cancer during osimertinib treatment - Ma, Qizhi; Shu, Pei; Zhou, Kexun; Wang, Yongsheng (Frontiers in Oncology, 2023)
We present a case of a woman with non-small cell lung cancer (NSCLC) who experienced disease progression during treatment with the epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI) osimertinib due to an unplanned pregnancy. Given the risk of tumor progression, the patient underwent an artificial abortion. However, disease deterioration occurred shortly after termination of the pregnancy, with severe chest pain, increased dyspnea, and pleural effusion. After positive rescue measures, including emergency thoracic drainage, thoracentesis and oxygen uptake, her symptoms improved. Considering pregnancy as an immune escape physiological process, the patient continued treatment with osimertinib, and a partial response (PR) lasting 16 months was observed. Therefore, this case highlights the importance of being vigilant about the rapid development of the tumor after delivery in pregnant patients with EGFR-mutation lung cancer and taking preventive measures to cope with various emergencies.